Creating a Cleaned Dataset for Ease of Use - Saira Ahmed; Daniel S Thayer; Muhammad A Elmessary; Ieuan Scanlon; Etienne Badoche (International Journal of Population Data Science, 2024)
Objective The Welsh Longitudinal General Practice (WLGP) dataset contains over 4 billion records. Due to the size and the need to filter the dataset to get the necessary general practice interaction results, query performance is poor. To overcome this, a ‘cleaned’ version of the dataset needed to be created.